2009
DOI: 10.1134/s1063772909070026
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of protostellar clouds and their observational properties

Abstract: A physical model and two-dimensional numerical method for computing the evolution and spectra of protostellar clouds are described. The physical model is based on a system of magneto-gasdynamical equations, including ohmic and ambipolar diffusion, and a scheme for calculating the thermal and ionization structure of a cloud. The dust and gas temperatures are determined during the calculations of the thermal structure of the cloud. The results of computing the dynamical and thermal structure of the cloud are use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Indeed for gas densities lower than 10 5 H/cm 3 , a mild dust-gas coupling is expected. In this case, the dust grains are usually colder than the gas by 2−3 K, especially when the grain growth is taken into account because it further decreases the dust-gas coupling (Zhilkin et al 2009;Juvela & Ysard 2011;Nielbock et al 2012). This indicates that the gas temperature in Pagani et al (2010a) may have been slightly underestimated.…”
Section: Third Cutmentioning
confidence: 99%
“…Indeed for gas densities lower than 10 5 H/cm 3 , a mild dust-gas coupling is expected. In this case, the dust grains are usually colder than the gas by 2−3 K, especially when the grain growth is taken into account because it further decreases the dust-gas coupling (Zhilkin et al 2009;Juvela & Ysard 2011;Nielbock et al 2012). This indicates that the gas temperature in Pagani et al (2010a) may have been slightly underestimated.…”
Section: Third Cutmentioning
confidence: 99%
“…Hotzel et al 2002a;Bergin et al 2006), and generally one would expect both the gas and the dust temperature to be tightly coupled in the core centre, where they experience densities of n H ≥ 10 5 cm −3 (e.g. Lesaffre et al 2005;Zhilkin et al 2009), with the strength of the coupling gradually increasing already from n H ≈ 10 4 cm −3 (Goldsmith 2001). However, Bergin et al (2006) found evidence that this might not be necessarily the case.…”
Section: The Temperature Distributionmentioning
confidence: 99%
“…This can lead to diverging gas and dust temperatures in the centre of dense cores (e.g. Zhilkin et al 2009). According to Bergin et al (2006), this can only be explained by a reduced gas-to-dust coupling in the centre of B68, especially when -as in this case -the gas is strongly depleted.…”
Section: The Temperature Distributionmentioning
confidence: 99%
“…This is a two-dimensional code for modelling the axysymmetric MHD flows (Dudorov et al 1999;Zhilkin et al 2009). The code is based on the explicit quasi-monotonic TVD-scheme of high order of accuracy.…”
Section: Numerical Codementioning
confidence: 99%